An Evaluation of the Public Schools of the District of Columbia: Reform in a Changing Landscape - National Research Council (The National Academies Press, 2015)
An Evaluation of the Public Schools of the District of Columbia is a comprehensive five-year summative evaluation report for Phase Two of an initiative to evaluate the District of Columbia's public schools. Consistent with the recommendations in the 2011 report A Plan for Evaluating the District of Columbia's Public Schools, this new report describes changes in the public schools during the period from 2009 to 2013. An Evaluation of the Public Schools of the District of Columbia examines business practices, human resources operations and human capital strategies, academic plans, and student achievement. This report identifies what is working well seven years after legislation was enacted to give control of public schools to the mayor of the District of Columbia and which areas need additional attention.

The Integration of Immigrants into American Society - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
The United States prides itself on being a nation of immigrants, and the country has a long history of successfully absorbing people from across the globe. The integration of immigrants and their children contributes to our economic vitality and our vibrant and ever changing culture. We have offered opportunities to immigrants and their children to better themselves and to be fully incorporated into our society and in exchange immigrants have become Americans - embracing an American identity and citizenship, protecting our country through service in our military, fostering technological innovation, harvesting its crops, and enriching everything from the nation's cuisine to its universities, music, and art. Today, the 41 million immigrants in the United States represent 13.1 percent of the U.S. population. The U.S.-born children of immigrants, the second generation, represent another 37.1 million people, or 12 percent of the population. Thus, together the first and second generations account for one out of four members of the U.S. population. Whether they are successfully integrating is therefore a pressing and important question. Are new immigrants and their children being well integrated into American society, within and across generations? Do current policies and practices facilitate their integration? How is American society being transformed by the millions of immigrants who have arrived in recent decades? To answer these questions, this new report from the National Academies of Sciences, Engineering, and Medicine summarizes what we know about how immigrants and their descendants are integrating into American society in a range of areas such as education, occupations, health, and language.

Using Existing Platforms to Integrate and Coordinate Investments for Children: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine; Centre for Health Education and Health Promotion; and Wu Yee Sun College of the Chinese University of Hong Kong - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
The integration and coordination of health, education, nutrition, social protection, and other services have the potential to improve the lives of children and their caregivers around the world. However, integration and coordination of policies and programs affecting early childhood development can create both risks and benefits. In different localities, these services are more or less effective in achieving their objectives. They also are more or less coordinated in delivering services to the same recipients, and in some cases services are delivered by integrated multisectoral organizations. The result is a rich arena for policy analysis and change and a complex challenge for public- and private-sector organizations that are seeking to improve the lives of children. To examine the science and policy issues involved in coordinating investments in children and their caregivers, the Forum on Investing in Young Children Globally held a workshop in Hong Kong on March 14-15, 2015. Held in partnership with the Centre for Health Education and Health Promotion and Wu Yee Sun College of the Chinese University of Hong Kong, the workshop brought together researchers, policy makers, program practitioners, and other experts from 22 countries. This report highlights the presentations and discussions of the event.

Investing in the Health and Well-Being of Young Adults - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Young adulthood - ages approximately 18 to 26 - is a critical period of development with long-lasting implications for a person's economic security, health and well-being. Young adults are key contributors to the nation's workforce and military services and, since many are parents, to the healthy development of the next generation. Although 'millennials' have received attention in the popular media in recent years, young adults are too rarely treated as a distinct population in policy, programs, and research. Instead, they are often grouped with adolescents or, more often, with all adults. Currently, the nation is experiencing economic restructuring, widening inequality, a rapidly rising ratio of older adults, and an increasingly diverse population. The possible transformative effects of these features make focus on young adults especially important. A systematic approach to understanding and responding to the unique circumstances and needs of today's young adults can help to pave the way to a more productive and equitable tomorrow for young adults in particular and our society at large. Investing in The Health and Well-Being of Young Adults describes what is meant by the term young adulthood, who young adults are, what they are doing, and what they need. This study recommends actions that nonprofit programs and federal, state, and local agencies can take to help young adults make a successful transition from adolescence to adulthood. According to this report, young adults should be considered as a separate group from adolescents and older adults. Investing in The Health and Well-Being of Young Adults makes the case that increased efforts to improve high school and college graduate rates and education and workforce development systems that are more closely tied to high-demand economic sectors will help this age group achieve greater opportunity and success. The report also discusses the health status of young adults and makes recommendations to develop evidence-based practices for young adults for medical and behavioral health, including preventions. What happens during the young adult years has profound implications for the rest of the life course, and the stability and progress of society at large depends on how any cohort of young adults fares as a whole. Investing in The Health and Well-Being of Young Adults will provide a roadmap to improving outcomes for this age group as they transition from adolescence to adulthood.

Opportunities to Promote Children's Behavioral Health: Health Care Reform and Beyond: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
The Patient Protection and Affordable Care Act (ACA), which was signed into law in 2010, has several provisions that could greatly improve the behavioral health of children and adolescents in the United States. It requires that many insurance plans cover mental health and substance use disorder services, rehabilitative services to help support people with behavioral health challenges, and preventive services like behavioral assessments for children and depression screening for adults. These and other provisions provide an opportunity to confront the many behavioral health challenges facing youth in America. To explore how the ACA and other aspects of health care reform can support innovations to improve children's behavioral health and sustain those innovations over time, the Forum on Promoting Children's Cognitive, Affective, and Behavioral Health held a workshop on April 1-2, 2015. The workshop explicitly addressed the behavioral health needs of all children, including those with special health needs. It also took a two-generation approach, looking at the programs and services that support not only children but also parents and families. This report summarizes the presentations and discussions of this workshop.